Прогноз газоносності вугільних пластів Тяглівського родовища Львівсько-Волинського басейну - Явний, П.; Книш, І.; Бучинська, І.; Бик, С. (Геологія і геохімія горючих копалин, 2009)
На прикладі вивчення вугільних пластів спрогнозовано газоносність Тяглівського родовища. Побудовано цифрові карти, які показують реальну картину газоносності основних робочих вугільних пластів, що розширить можливості вирішення завдань наукових та гірничо-видобувних організацій, які стосуються вивчення газоносності Львівсько-Волинського басейну загалом. Вірогідні запаси вуглеводневих газів цього родовища становлять понад 7,5 млрд м3. На основі встановлених регресивних рівнянь залежності між газоносністю (об.ємом газу) та глибиною залягання вугільного пласта з допустимою похибкою можна підрахувати його прогнозну газоносність без визначення її прямими методами. Considerable resources of combustible gases (methane in the main and its homologues to a lesser extent) are known to occur in the coal-bearing thickness of the coalfields of the Lviv-Volyn basin. Taking into account insignificant reserves of hydrocarbon gases, the development of the extraction and utilization of methane from coalbeds and enclosing rocks of the coal-bearing thickness becomes the matter of current. At the same time, the mine methane creates a threat to safety of coal producing works in mines, and it is one of the main pollutants of the environment. Coalbed methane should be considered as an alternative power source commensurable to the natural gas. Taking studies of the Tyagliv field as an example, it was possible to predict the gas presence in coalbeds. We have compiling numerical maps showing the realistic picture of main working seams which will broaden the possibilities of the solution of scientific and mining organizations. This is of the sections of work on studying gas presence of the Lviv-Volyn basin on the whole. Expected reserves of the coal-bearing thickness of the Tyagliv field of the Lviv-Volyn basin are estimated to be 7.5 bn m3. We have established the dependence equations between the gas presence (gas volume) and a depth of occurrence of the coalbed. On the basis of these regressive equations with admissible error one can calculate the expected gas presence in the coalbed without using direct method. This employment will be effective in predicting gas presence of the coalbeds of the Tyagliv field with certainty.